Influence of Organisational Culture on Insourcing Decisions: Comparative Insights from Shared Value and Multi-Sourcing Models - Michael Mncedisi Willie; Zwanaka James Mudara (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Kuningan, 2026)
Background: Insourcing the internal performance of organisational functions has evolved from an operational choice to a strategic lever reflecting organisational culture, values, and long-term objectives. In healthcare, insourcing decisions influence service quality, member satisfaction, and operational efficiency, highlighting the need to align decisions with organisational culture. Objectives: This study investigated how organisational culture shaped insourcing decisions and compared the efficacy of the shared value and multi-sourced models in aligning cultural, strategic, and operational priorities. Methods: A qualitative, multiple case study design examined two Health Insurance companies in South Africa, HealthCare and WellTrust. Data were collected through document analysis of annual reports, strategic plans, and operational guidelines, complemented by secondary sources such as policy documents and industry analyses. Thematic analysis guided the identification of patterns in how organisational culture informed insourcing strategies. Results: HealthyCare, guided by a Shared Value Model, prioritises mission, values, and member-centric outcomes, resulting in high employee engagement and stakeholder satisfaction, with moderate operational efficiency. WellTrust, following a Multi-Sourced Model, emphasises performance metrics and capacity, achieving high operational efficiency but only moderate engagement and slightly lower stakeholder satisfaction. Comparative analysis suggests hybrid approaches, integrating cultural alignment with operational performance metrics, provide a balanced strategy for sustainable and effective insourcing. Conclusions: Organisational culture is critical in shaping insourcing decisions, which affect employee engagement, operational performance, and stakeholder satisfaction. The integration of Shared Value and Multi-Sourced approaches enabled the balance of cultural alignment with operational effectiveness, providing a structured framework to guide strategic, ethical, and sustainable decision-making in healthcare management.